Making Harlem visible: race, photography and the American city, 1915-1955 - Ings, Richard (2004)
In his philosophical treatise on photography, The Engine of Visualization: Thinking Through Photography, Patrick Maynard makes a detailed and convincing case that photography, like other technologies, has been developed to 'amplify our powers to do things' - in this case to imagine. Photography is, fundamentally, an 'imagining technology' and photographs - 'depictive pictures' - gain their extraordinary vividness from the efficiency of this technology: